Accuracy of Transcutaneous Carbon Dioxide Levels in Comparison to Arterial Carbon Dioxide Levels in Critically Ill Children - Bhalla, Anoopindar K; Khemani, Robinder G; Hotz, Justin C; Morzov, Rica P; Newth, Christopher Jl (Respiratory care, 2019)
Widespread use of transcutaneous P (P ) monitoring is currently limited by concerns many practitioners have regarding accuracy. We compared the accuracy of P with that of P measurements in critically ill children, and we investigated whether clinical conditions associated with low cardiac output or increased subcutaneous tissue affect this accuracy. We performed a single-center prospective study of critically ill children placed on transcutaneous monitoring. There were 184 children enrolled with paired P and P values. Subjects had a median age of 31.8 mo (interquartile range 3.5-123.3 mo). Most children were mechanically ventilated ( = 161, 87.5%), and many had cardiac disease ( = 76, 41.3%). The median P was 44 mm Hg (interquartile range 39-51 mm Hg). The mean bias between P and P was 0.6 mm Hg with 95% limits of agreement from -13.6 to 14.7 mm Hg. The P and P were within ±5 mm Hg in 126 (68.5%) measurements. In multivariable modeling, cyanotic heart disease (odds ratio 3.5, 95% CI 1.2-10, = .02) and monitor number 2 (odds ratio 3.8 95% CI 1.3-10.5, = .01) remained associated with P ≥ 5 mm Hg higher than P . Serum lactate, fluid balance, renal failure, obesity, vasoactive-inotrope score, and acyanotic heart disease were not associated with high or low P values. In 130 children with a second paired P and P measurement, predicting the second measured P by subtracting the initial observed difference between the P and P from the subsequent measured P decreased the mean bias between observed and predicted P to 0.2 mm Hg and the 95% limits of agreement to -9.4 to 9.7 mm Hg. P provides an acceptable estimate of P in many critically ill children, including those with clinical conditions that may be associated with low cardiac output or increased subcutaneous tissue, although it does not perform as well in children with cyanotic heart disease. P may be a useful adjunct monitoring method, but it cannot reliably replace P measurement.